Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Untuk Berinvestasi Di Pasar Modal (Studi Empiris Pada Mahasiswa Akuntansi Di Universitas Swasta Di Kota Bengkulu) - Heldi Sahputra; Ahmad Junaidi; Meido Ade Putra (Universitas Muhammadiyah Bengkulu, 2020)
ABSTRACTÂ The background in this research is the lack of interest of students to invest in the capital market. The number of students who invest in the Investment Gallery has not reached 10% of the total number of students at the Private University in Bengkulu City. The problem in this research is to discuss whether the variables of knowledge, motivation, minimal capital, return, risk and benefits affect the interest of students in investing in the capital market. The purpose of this study is to determine whether the variables have effect on knowledge, motivation, minimal capital, return, risk, and benefits of students' interest in investing in the capital market. The research was a type of quantitative research, using the sample of 265 students. The sampling technique was done by using the sample size table developed by Isaac and Michael. The data collection techniques used was a questionnaire. The data was analyzed using classical assumptions, t- test, f-test, and multiple linear regression. Based on the results of multiple linear regression obtained by the regression equation Y = 0.682 + 0.178 X1 + 0.083 X2 + 0.133 X3 + 0.271 X4 + 0.078 X5 + 0.134 X6 + e. The results of the hypothesis test simultaneously showed the variables of knowledge, motivation, minimal capital, return, risk and benefits have a positive and significant effect (sig Î± = 0,000) on the interest of students investing in the capital market. Partially, knowledge variables (sig Î± = 0, 001), motivation (sig Î± = 0, 049), minimal capital (sig Î± = 0.003), return (sig Î± = 0, 000), risk (sig Î± = 0, 005), and the benefits (sig Î± = 0, 001) have a positive and significant effect on the interests of students investing in the capital market. From the results of the t- test carried out, it can be concluded that the variable of knowledge, motivation, minimal capital, return, risk and benefits partially affect the interest of students to invest in the capital market. F-test results show variable knowledge, motivation, minimal capital, return, risk and benefits simultaneously affect the interest of students to invest in the capital market.Keywords: Knowledge, Motivation, Minimal Capital, Return, Risk, Benefits, Investment Interest.